PERKEMBANGAN PARTAI POLITIK PADA MASA ORDE BARU (1966-1998) - Arief Hidayat (Jurnal Ilmiah Mimbar Demokrasi, 2018)
This study discussed the development of political parties in Indonesia during the New Order era. During this time political freedom was restricted, mass participation is suppressed, the electoral process was controlled by the government and hardly provided the opportunity for public scrutiny. The only political parties are PPP (Development Unity Party), PDI (Indonesian Democracy Party) and Golongan Karya, which are government political parties. In the view of the government the failure of development so far has come from the political sector, especially political parties. The policy was adopted as part of an efforts to achieve political stability in order to realize national development. In other words democracy is sacrificed for the benefit of economic development.